Cross-Coupling Reactions as Valuable Tool for the Preparation of PET Radiotracers - Marc Pretze; Constantin Mamat; Philipp Große-Gehling (Molecules, 2011)
The increasing application of positron emission tomography (PET) in nuclear medicine has stimulated the extensive development of a multitude of new radiotracers and novel radiolabeling procedures with the most prominent short-lived positron emitters carbon-11 and fluorine-18. Radiolabeling with these radionuclides represents a remarkable challenge. Special attention has to be paid to synthesis time and specific labeling techniques due to the short physical half life of the respective radionuclides 11C (t1/2 = 20.4 min) and 18F (t1/2 = 109.8 min). In the past, numerous transition metal-catalyzed reactions were employed in organic chemistry, even though only a handful of these coupling reactions were adopted in radiochemical practice. Thus, the implementation of modern synthesis methods like cross-coupling reactions offers the possibility to develop a wide variety of novel radiotracers. The introduction of catalysts based on transition metal complexes bears a high potential for rapid, efficient, highly selective and functional group-tolerating incorporation of carbon-11 and fluorine-18 into target molecules. This review deals with design, application and improvement of transition metal-mediated carbon-carbon as well as carbon-heteroatom cross-coupling reactions as a labeling feature with the focus on the preparation of radiolabeled compounds for molecular imaging.